Gross Mismatch and Employee Performance of State Ministries in Anambra State, Nigeria - Okeke, C.O.; Mgbemena, G. C.; Anabaraonye, C. L.; C. Omaliko, K.; Gbenga, W.; Onwunanzo, E. V. (British Journal of Marketing Studies, 2025)
This study investigates the relationship between gross mismatch and employee performance in Ministries of Anambra State, focusing on education-job mismatch and skill-task mismatch. Anchored on Human Capital Theory, the study adopted a descriptive survey research design with sample size of 367 using Taro Yamane formula from a population of 4,527 staff across five key ministries.329 out of 367 were found valid and used for analysis. Data were collected through structured questionnaires were analyzed using Pearson Product Moment Correlation Coefficient via SPSS. The findings reveal a significant negative relationship between education-job mismatch and employee performance (r = -0.871, t = 14.842, ? = -0.752, p = 0.021), indicating that a one-unit increase in mismatch leads to a -0.752-unit decline in performance. Similarly, skill-task mismatch was negatively correlated with employee performance (r = -0.720, t = 10.231, ? = -0.645, p = 0.013), with a one-unit increase resulting in a -0.645-unit decline. These mismatches collectively explained 75.9% and 51.8% of the variance in employee performance, respectively. The study concludes that gross mismatch undermines organizational efficiency, as the misalignment of qualifications and job roles hampers productivity and quality of service delivery. It recommends implementing merit-based recruitment and regular training programs to align employee skills with job demands, thus fostering improved performance and organizational success.